Comparative Study on Criminal Provisions on Regional Regulations Concerning Exclusive Breastfeeding - Windayani, Tisa (Indonesian Comparative Law Review, 2018)
Infant’s right on exclusive breastfeeding has been protected on Law No. 36/2009 on Health. One of the measurements in its protection is by using criminal provision. It is stated in Art. 200 and 201, each of which has criminal sanction to those obstructing the exclusive breastfeeding program. As an effort to implement this national policy, quite a numerous of provinces or even lower administrative regions had issued regulations concerning the same matter. Some of them have criminal provision as well, as can be seen in City Regulation of Cirebon No. 4/2016 on Early Initiation and Exclusive Breastfeeding and also in the City Regulation of Semarang No. 5/2014 on Early Initiation and Exclusive Breastfeeding. This paper will assess specifically the criminal provisions on those regional laws in a comparative perspective. The selection of the two laws is based on the preliminary study which found a quite unique form of criminal provisions on each laws. The analysis is also be based on art 200 and 201 Law No. 36/2009 and its derivative regulations as a normative measurement in national level, with which the two regional laws must be in line to. This research found that there are quite a significance differences between the two laws especially regarding the form of action that is criminally regulated. Variation also found on how the two laws fulfil what is demanded by the national criminal policy.